Adaptive Reuse of a Complex of Three Historic Houses in the Dardasht Neighbourhood of Isfahan, Iran - Narmin Babazadeh Asbagh (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Isfahan is a gorgeous historic city in Iran, well-known for the glorious buildings of the Safavid era. Dardasht is one of the significant neighbourhoods in Isfahan, consisting of elegant houses and valuable cultural heritage. There is a complex of three historic houses, Habib Abadi, Katiraei (Kadkhoda), and Badiol Sanaye, which are abandoned. This article proposes adaptive reuse to preserve this historic complex in the Dardasht neighbourhood of Isfahan. After comprehensive research about Isfahan, the neighbourhood of Dardasht, and the current situation of the houses, proposals for the adaptive reuse of this historic complex are suggested comprehensively. This historic research is based on qualitative and quantitative methods and the author’s observations. The results of this article can be useful for preservationists and conservationists in the field of cultural heritage, and also architects and interior designers in designing in the historical context of ancient cities.